(untitled) (Web of Teachers: Inderscience Research, 2025)
In this article, the issues of forming media literacy and information culture based on the organization of media education are extensively analyzed. In the era of globalization, as the influence of the Internet, social networks, and mass media expands in the global arena, the risk of moral crisis is also increasing. In the article, first of all, along with the numerical growth of the global information flow, it will be explained on a scientific and theoretical basis what can be caused by a sharp change in its content.